In Situ Study of the Gas‐Phase Electrolysis of Water on Platinum by NAP‐XPS1. Issue 44 (17th September 2013) - Arrigo, Rosa; Hävecker, Michael; Schuster, Manfred E.; Ranjan, Chinmoy; Stotz, Eugen; Knop‐Gericke, Axel; Schlögl, Robert
<x xml:space="preserve">Abstract</x> Chasing down the active state: Near‐ambient‐pressure X‐ray photoelectron spectroscopy was used to study the surface of a Pt electrode during the oxygen evolution reaction (OER). A hydrated Pt metal phase with dissolved oxygen in the near‐surface region is OER‐active and considered to be the precursor of the analytically detected PtO2, which is in fact the deactivation product of the electrode.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>